A Prostacyclin-sparing Effect of Indobufen vs. Aspirin - Caterina, R De; Giannessi, D; Bernini, W; Lazzerini, G; Lavezzari, M; Stragliotto, E; Biagi, G; Coccheri, S (Thrombosis and Haemostasis, 1996)
Indobufen ((±)-2-[p-(l-oxo-2-insoindolinyl)-phenyI]-butyric acid, indo) is a drug inhibiting platelet function by a reversible block of the arachidonic acid metabolism at the level of cyclooxygenase. Since tolerability profile of such drugs is mostly linked to extra-platelet cyclooxygenase inhibition, we prospectively evaluated the extent of platelet and extra-platelet cyclooxygenase inhibition by in vivo administration of indo in comparison with ASA. We assessed the effects of the two drugs on the ex vivo generation of TXB2 and 6-keto-PGFlΑ in whole blood, as indices of the production of TXA2 and PGI2 (prostacyclin), respectively, either after spontaneous clotting at 37° C for 1 h (Study 1) or after the addition of 2 Μg/ml collagen (Study 2). Generation of 6-keto-PGFlΑ in whole blood is a mixed index of platelet and extra-platelet cyclooxygenase activity, deriving from both platelet and white blood cell arachidonic acid metabolization. Fifteen patients with ischemic heart disease and baseline serum TXB2 levels > 300 ng/ml were allocated to receiving one single administration of either indobufen 200 mg (n = 6) or aspirin 500 mg (n = 9). Whole blood prostanoid generation was assessed at 0,1,2,4,6, 8,12 and 24 h after drug administration (Study 1). Ten healthy male volunteers were allocated to a double-blind, randomized crossover comparison of indo 200 mg b.i.d. vs. ASA 300 mg/d for 7 days (Study 2). Prostanoid generation and whole blood platelet aggregation were performed before and at the end of each study period (Day 0 and Day 7). At each time-point after single dose administration (Study 1), indobufen caused less % inhibition of whole blood 6-keto-PGFlΑ than of TXB2. At 2 h, TXB2 was reduced to a similar extent after ASA (98 ± 4%) and indo (97 ± 6%) (p = N.S.), while inhibition of 6-keto-PGFla was clearly different (> 98% after ASA, 81 ± 2.5% after indo, p < 0.01). After one week of ASA or indo (Study 2) the maximum extent of whole blood platelet aggregation was similarly inhibited (from 17.2 ± 1.4 ohms to 3.6 ± 1.3 ohms with ASA; from 18.3 ± 1.0 ohms to 1.6 ± 0.7 ohms with indo (p ASA vs. indo = N. S.). Despite equal inhibition of whole blood TX production after collagen (from 49.0 ± 4.3 ng/ml to 1.1 ± 0.6 ng/ml with ASA, from 49.8 ± 1.3 ng/ml to 1.4 ± 0.6 ng/ml with indo), again, however, 6-keto-PGFlΑ production was less affected by indo than by ASA (from 409 ± 30 pg/ml to 37 ± 13 pg/ml with ASA, inhibition = 91%; from 396 ± 35 to 318 ± 40 with indo, inhibition = 20%). These differential effects of indo and ASA might lead to a better platelet selectivity, tolerability and benefit/risk profile of indo vs. ASA, which are worthy of further assessment.